Screening of prenatal depression and anxiety among antenatal women and their association with fear of Coronavirus disease during the COVID-19 pandemic in Coastal Karnataka, India - Siddiqua, Ayesha; Poojari, Vidyashree Ganesh; Praharaj, Samir Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: A vulnerable population like pregnant mothers may have several concerns and anxieties about the impact of coronavirus disease 2019 (COVID-19) infection on pregnancy outcomes and the unborn fetus. However, there is no definitive information on the effect of COVID‐19 on the mental health of pregnant women in our population. We aimed to study the prevalence of depression, anxiety, and COVID-19 related anxiety among antenatal women during the COVID-19 pandemic. Methods: This was a cross-sectional study performed on all antenatal women irrespective of their trimester. Depression, anxiety and COVID-19 related anxiety were assessed using Patient Health Questionnaire-9, Generalized Anxiety Disorder-7 and COVID-19 Anxiety Syndrome scale respectively. Results: 381 antenatal women responded to the questionnaire. Though the prevalence of clinically significant anxiety and depression was 1.3% and 1%, 74% of them had subsyndromal anxiety and 80.6% had subsyndromal depression. Those with significant anxiety scores had higher COVID-19 anxiety. In contrast, those with significant depression had lower COVID-19 anxiety. Antenatal women who feared of various complications in pregnancy due to COVID-19 (like preterm birth, anomalous baby, fetal growth restriction, fear of getting infected with Coronavirus) had significantly higher COVID-19 anxiety. Conclusions: The prevalence of clinically significant anxiety and depression was 1.3% and 1%. However, three fourth of the participants suffered from subsyndromal anxiety and depression. Therefore, there is a need to identify antenatal women with subsyndromal anxiety and depression and provide psychosocial support to them during the crisis. Good communication, reassurance, providing care and support to pregnant women should be prioritized during the COVID-19 pandemic to avoid increased levels of anxiety and depression.